Measurements of electron transport in liquid and gas Xenon using a laser-driven photocathode - Njoya, O.; Tsang, T.; Tarka, M.; Fairbank, W.; Kumar, K. S.; Rao, T.; Wager, T.; Kharusi, S. Al; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
Measurements of electron drift properties in liquid and gaseous xenon are reported. The electrons are generated by the photoelectric effect in a semi-transparent gold photocathode driven in transmission mode with a pulsed ultraviolet laser. The charges drift and diffuse in a small chamber at various electric fields and a fixed drift distance of 2.0 cm. At an electric field of 0.5 kV/cm, the measured drift velocities and corresponding temperature coefficients respectively are 1.97±0.04mm∕μs and (−0.69±0.05)%/K for liquid xenon, and 1.42±0.03mm∕μs and (+0.11±0.01)%/K for gaseous xenon at 1.5 bar. In addition, we measure longitudinal diffusion coefficients of 25.7±4.6 cm2/s and 149±23 cm2/s, for liquid and gas, respectively. The quantum efficiency of the gold photocathode is studied at the photon energy of 4.73 eV in liquid and gaseous xenon, and vacuum. These charge transport properties and the behavior of photocathodes in a xenon environment are important in designing and calibrating future large scale noble liquid detectors.
CRIS-Team Scopus Importer:2020-05-29